2019
DOI: 10.3390/app10010070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Input on Formability, Microstructure, and Properties of Al–7Si–0.6Mg Alloys Deposited by CMT-WAAM Process

Abstract: In order to improve the forming efficiency of Al–7Si–0.6Mg fabricated by wire and arc additive manufacturing process (WAAM), wire with a diameter of 1.6 mm was selected as the raw material. The effect of heat input on the formability, microstructure, and properties of the WAAM alloy was investigated, and the forming model was established. The WAAM alloys were characterized by electronic universal testing, scanning electron microscopy, energy spectrum analysis, and metallographic microscopy. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The Al-7Si-0.6Mg (4220) alloy is suitable for melting-based processing without tendency to crack [ 128 ]. Thus, these alloys are well-suited for WAAM combined with artificial aging [ 129 , 130 ]. Yang et al showed that 4220 in as-deposited state has a relatively poor tensile strength of 130 , but can be raised to 350 in T6 state [ 131 , 132 ].…”
Section: Aluminum Alloys For Waammentioning
confidence: 99%
“…The Al-7Si-0.6Mg (4220) alloy is suitable for melting-based processing without tendency to crack [ 128 ]. Thus, these alloys are well-suited for WAAM combined with artificial aging [ 129 , 130 ]. Yang et al showed that 4220 in as-deposited state has a relatively poor tensile strength of 130 , but can be raised to 350 in T6 state [ 131 , 132 ].…”
Section: Aluminum Alloys For Waammentioning
confidence: 99%
“…Погонну енергію для експериментальних пар параметрів (рисунок 6) було визначено за наступною формулою [6]:…”
Section: матеріали і методиunclassified
“…Visually the microstructure is comparable to the microstructures reported in Refs. [20,21], which were fabricated by single wire WAAM but differs significantly from microstructures observed after selective laser melting (SLM) [22].The microstructures obtained after SLM are dominated by the severe nonequilibrium condition of the feedstock alloy powders and the subsequent intrinsic heat treatment being repetitive in nature, but due to the particularly small melt pool, cooling rates are much higher than during WAAM. EDX analysis was used for the identification of additional constituents visible in Fig.…”
Section: Microstructure and Phase Formationmentioning
confidence: 99%